PENGEMBANGAN PETUNJUK PRAKTIKUM MIKROBIOLOGI PROGRAM STUDI PENDIDIKAN BIOLOGI - Trio Ageng Prayitno (Biota, 2017)
The learning process of mikrobiology requires a microbiological lab instruction. This is needed in practical activities in the Laboratory to provide mastery minds on and hands on the students. This research aims to produce a valid microbiological lab instructions. This research is a research & development. That model of development used 4D Thiagarajan. 4D model include define stage, design stage, develop stage, and desseminate stage. Limitation of the research is only at develop stage. The instrument of research used questionnaire validation and responses. Data of the research was percentage of validity. The results showed that a microbiological lab instruction was valid. Advice, a microbiological lab instruction can be used in the learning process of microbiology.